Association between state Medicaid expansion status and naloxone prescription dispensing - Sohn, Minji (Health Serv Res, 2020)
OBJECTIVE: To test whether Medicaid expansion is associated with (a) a greater number of naloxone prescriptions dispensed and (b) a higher proportion of naloxone prescriptions paid by Medicaid. DATA SOURCES/STUDY SETTING: We used the IQVIA National Prescription Audit to obtain data on per state per quarter naloxone prescription dispensing for the period 2011‐16. STUDY DESIGN: In this quasi‐experimental design study, the impact of Medicaid expansion on naloxone prescription dispensing was examined using difference‐in‐difference estimation models. State‐level covariates including pharmacy‐based naloxone laws (standing/protocol orders and direct authority to dispense naloxone), third‐party prescribing laws, opioid analgesic prescribing rates, opioid‐involved overdose death rates, and population size were controlled for in the analysis. PRINCIPAL FINDINGS: Medicaid expansion was associated with 38 additional naloxone prescriptions dispensed per state per quarter compared to nonexpansion controls, on average (P = .030). Also, Medicaid expansion resulted in an average increase of 9.86 percent in the share of naloxone prescriptions paid by Medicaid per state per quarter (P < .001). CONCLUSIONS: Our study found that Medicaid expansion increased naloxone availability. This finding suggests that it will be important to consider naloxone access when making federal‐ and state‐level decisions affecting Medicaid coverage.